Does rationing really backfire? A critical review of the literature on license-plate-based driving restrictions. Issue 5 (3rd September 2022) - Guerra, Erick; Sandweiss, Andrew; Park, Seunglee David
ABSTRACT: Policies limiting the number of days vehicles are permitted to circulate based on the last digit of their license plates have experienced a resurgence in popularity, particularly in Chinese cities. This paper provides a critical review of the literature on license-plate-based driving restrictions. Of the 235 papers reviewed, most (152) only briefly mention license-plate-based restriction programmes to describe contextual conditions or provide an example of a policy that influences driving or vehicle purchases. Reviewing forty empirical papers, we find a divided literature on whether and where license-plate-based driving restrictions reduce local pollution or congestion. Some differences in findings likely relate to differences in research design or outcome measurement. Variations in policy design, enforcement, and other local conditions also play an important role. We next review findings about the multiple legal and illegal strategies households employ in response to driving restrictions. The second- car hypothesis, which posits that restriction policies backfire and lead to increased local pollution due to households purchasing second cars with different final license-plate digits, has become particularly popular. Evidence for the hypothesis, however, is mixed. Households employ a range of other behavioural responses, such as shuffling driving trips to specific days and driving in lightly policed areas, that likely attenuate the effectiveness of license-plate-based driving restrictions. As a result, researchers and policymakers should not expect to find a 20% reduction in pollution or congestion from banning a fifth of vehicles from the road. Improving policy effectiveness will likely require policymakers to address intended and unintended behavioural responses through additional mechanisms.